Local Cultural Values : Practicality Test of E-LKS Based on Peusijuek Tradition as An Embodiment of Pancasila Student Profile Strengthening Project (P5) - Sukirno Sukirno; Inge Ayudia; Juliati Juliati; Nursamsu Nursamsu; Rusliani Rusliani (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to develop E-LKS based on local cultural values of peusijeuk tradition as an embodiment Pancasila Student Profile Strengthening Project (P5). The research method used research and development with the ADDIE model, namely analysis, design, development, implementation, and evaluation. This research instrument used observation, a material expert questionnaire as a validation test, a product practicality test, an interview, and documentation. The data analysis technique usedqualitative and quantitative analysis. The research results obtained through expert validation tests of 87,5% were declared feasible for implementation. Meanwhile, the teacher responsed questionnaire resulted in an average practicality value of 82.82%, with a very practical category and the students' response questionnaire produced an average practicality score of 89.10%, with a very practical category. After conducting an assessment through several stages of assessment aspects, the peusijuek tradition-based E-LKS as the embodiment of the project to strengthen the profile of Pancasila students (P5) can be concluded to be categorized as very practical based on the results of the assessment by teachers and students as users.